Combustion dynamics analysis of a pressurized airblast swirl burner using proper orthogonal decomposition - Ghasemi, Alireza; Christou, Thomas; Kok, Jim B.W.; Stelzner, Björn; Zarzalis, Nikolaos (International journal of spray and combustion dynamics, 2024)
Jet fuel-fired combustors in aero gas turbine engines have switched to lean burn to decrease nitric oxide emissions in recent years as a result of strict emission regulations. Lean operating conditions, however, exhibit a heightened sensitivity to thermoacoustic instabilities and such burners require careful consideration in design and operation. Similar to natural gas-fired combustors, they exhibit thermoacoustic instabilities, but the characteristics are more complex and less well-studied. This paper presents a numerical investigation of an airblast jet fuel swirl burner operating with preheated air at lean pressurized conditions. In order to understand the acoustic characteristics of the in-house designed burner (Magister UT burner), detached eddy simulations are performed at relevant aero engine conditions. Simulation results are then analyzed by means of our internally developed parallel modal analysis package, PARAMOUNT, to perform proper orthogonal decomposition (POD) on large datasets. The resulting modes are inspected to highlight flow features of interest and their associated acoustic frequencies at unforced conditions. Single frequency acoustic forcing is employed to study the acoustic response of the burner to perturbations at similar frequencies to its precessing vortex core. We show that parallel computation of POD modes is a viable tool to investigate the main flow features of swirl burners and is suitable for highlighting the important acoustic frequencies without the need to employ fully compressible computational fluid dynamics solvers. Additionally, the analysis method reveals the ways in which various flow structures correlate with each other and how external perturbations modify them.